Controller’s guide to costing - Bragg, Steven M. (John Wiley & Sons, 2005)
Bragg has been the CFO or controller of four companies, as well as a consulting manager at Ernst & Young and auditor at Deloitte & Touche, and has written 20 books on accounting-related topics. He presents a practical text for controllers, treasurers, accountants, financial analysis personnel, and auditors, providing the necessary knowledge base for understanding a company's cost structure. Coverage includes discussion of every major costing methodology, including the traditional job and process costing concepts, direct costing, standard costing, and several inventory layering techniques; specialized costing methodologies; a costing systems summary identifying which technique to use for a different objective; and specific recommendations for key management decisions, such as outsourcing, cost reduction analysis, scrap costing, and capacity utilization